2010
DOI: 10.5539/ijbm.v5n10p20
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Structure Relationship from Functional and Relational Value to Behavior Intention: The Role of Satisfaction and Relationship Commitment

Abstract: Value is a subjective construct that varies between customers, cultures and at different times. Most of the research focus on the value of physical product/service and neglect the value of relationship. This study is the first to consider customer value in terms of both functional and relational aspect. The main objective of the study is to investigate the most prominent predictor of customer behavior intention and also to examine the indirect factors (functional value and relational value) relate to the respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 75 publications
3
16
0
Order By: Relevance
“…It also produced support for the conceptualization of loyalty based on cognitive and affective antecedents (Khan et al, 2010). Thus, the present study confirms that retail bank customers' perceived value includes (1) functional aspects of value as price, convenience, assurance and empathy and (2) aspects of brand appraisal as attitude toward brand and attitude toward organization.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…It also produced support for the conceptualization of loyalty based on cognitive and affective antecedents (Khan et al, 2010). Thus, the present study confirms that retail bank customers' perceived value includes (1) functional aspects of value as price, convenience, assurance and empathy and (2) aspects of brand appraisal as attitude toward brand and attitude toward organization.…”
Section: Discussionsupporting
confidence: 63%
“…Empirical studies have confirmed that social relations between a customer and an organization act as an emotional determinant in loyalty building (Dwyer et al, 1987). N. Khan et al (2010) justified the relation of value equity drivers (price and quality), commitment, satisfaction and attitude to communication with loyalty intentions in the banking industry and argued that the dimension of relationship value is missing in the scaling of the influence of value on loyalty intentions. L. J. C. Fiol et al (2011) investigated price, convenience, switching costs, product quality, service quality and service staff quality as value equity factors; image and reputation were chosen as the attributes of social value, whereas experience, personal attention and relationship value were chosen as the components of emotional value.…”
Section: Value As Multidimensional Conceptmentioning
confidence: 99%
“…Many of the studies (Wang et al, 2004;S anchez et al, 2006;Roig et al, 2006Roig et al, , 2013 have used or adapted Sweeney and Soutar's (2001) emotional value measure which includes items which cover affective states such as relaxation, feeling at ease, positive feeling from the service and contact personnel. Other authors (Lapierre, 2000;LeBlanc and Nguyen, 2001;Khan et al, 2010;Goldman, 2011) expand the emotional value to include relational value dimensions such as trust (Lapierre, 2000;Heinonen, 2009), solidarity (Lapierre, 2000); relational confidence (Khan et al, 2010); relational communication (LeBlanc and Nguyen, 2001;Khan et al, 2010); connectedness (Randall et al, 2011). From the authors' experiences as credit union members, practitioners and researchers, these dimensions would appear to better reflect the relationship between the member and the credit union.…”
Section: How Is Value Measured?mentioning
confidence: 99%
“…Byrne et al (2012) also identified a number of these dimensions in their research. Some of the authors mentioned above use the term relational rather than emotional value (Lapierre, 2000;Khan et al, 2010). We also use the term relational value in this paper, as we feel that it better expresses value in a credit union context.…”
Section: How Is Value Measured?mentioning
confidence: 99%
“…However, this study adopts Theory of Consumption Value by Sheth et al (1991) as it is considered to be excellent in analyzing the diverse traits and attributes of products through exploring customers' opinion, which fits the objective of this study. Among the studies conducted in Malaysia on the impact of customer perceived value on consumer's purchase intention includes Nor Asshidin, et al (2016), Ariffin, et al (2016), Younus et al (2015) and Khan, et al (2010) which focus on respective industrial context such as green products etc. These researches aimed to investigate the products offered by manufacturers and other context but not residential property market, hence, as mentioned earlier, it is the gap that needs to be filled in order to investigate the customer perceived value in the property market.…”
Section: Research Gapmentioning
confidence: 99%